Unsimplified Fraction

Geometry Level 2

If we have sin ( A + B ) cos ( A B ) = 1 + 5 1 5 \dfrac { \sin(A+B) }{ \cos(A-B) } =\frac { 1+5 }{ 1-5 } then find the value of tan ( π 4 A ) tan ( π 4 B ) . \tan\left(\dfrac { \pi }{ 4 } -A\right)\tan\left(\dfrac { \pi }{ 4 } -B\right).


The answer is -5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Ayush Verma
Dec 11, 2014

l e t π 4 A = P , π 4 B = Q sin ( A + B ) = cos ( P + Q ) cos ( A B ) = cos ( Q P ) 1 + 5 1 5 = cos ( Q + P ) cos ( Q P ) = cos P cos Q sin P sin Q cos P cos Q + sin P sin Q = 1 tan P tan Q 1 + tan P tan Q = 1 X 1 + X X = 5 let\quad \cfrac { \pi }{ 4 } -A=P,\cfrac { \pi }{ 4 } -B=Q\\ \\ \sin { \left( A+B \right) } =\cos { \left( P+Q \right) } \\ \\ \cos { \left( A-B \right) } =\cos { \left( Q-P \right) } \\ \\ \Rightarrow \cfrac { 1+5 }{ 1-5 } =\cfrac { \cos { \left( Q+P \right) } }{ \cos { \left( Q-P \right) } } \\ \\ \quad =\cfrac { \cos { P } \cos { Q } -\sin { P } \sin { Q } }{ \cos { P } \cos { Q } +\sin { P } \sin { Q } } \\ \\ \quad =\cfrac { 1-\tan { P } \tan { Q } }{ 1+\tan { P } \tan { Q } } =\cfrac { 1-X }{ 1+X } \\ \\ \Rightarrow X=-5

Please,let me know is the answer is -5 or there is a mistake in my calculation.

Thanks.

Thanks, I have updated the answer to -5.

Calvin Lin Staff - 6 years, 6 months ago

Even I got -5

Aneesh Kundu - 6 years, 6 months ago

I also got -5

Kumar Krish - 2 years, 4 months ago
Incredible Mind
Jan 19, 2015

easiest way is to simply put B=0 ..hence tanA=-1.5..then just expand second required expression ANS was -5

Simplifying the given equation (Sin A Cos B + Cos A Sin B)/(Cos A Cos B + Sin A Sin B) = ( Tan A + Tan B)/( 1 + Tan A Tan B) = -3/2

Hence Tan A + Tan B = (-3/2)(Tan A Tan B + 1)

Now Tan (Pi/4 - A) Tan (Pi/4 - B) = ((1 - Tan A)/(1 + Tan A) ((1 - Tan B)/(1 + Tan B))

=( 1- (Tan A + Tan B) + Tan A Tan B)/( 1 + (Tan A + Tan B) + Tan A Tan B)

= ( 1 + (3/2)( Tan A Tan B + 1) + Tan A Tan B)/( 1 - (3/2) (Tan A Tan B + 1) + Tan A Tan B)

= (5/2) ( 1 + Tan A Tan B)/ (-1/2) (1 + Tan A Tan B) = -5

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...